Heat transfer and friction near the rotating cylinder with the duct of fluid through it surface - Юр’єв, Сергій Олександрович (Technology audit and production reserves, 2012)
The results of a numerical study of momentum and heat transfer intensity in a flow outside rotating permeable cylinders are described. The effect of liquid flow rate through the surface of a rotating cylinder on the hydrodynamic losses and heat transfer is fixed